(untitled) (Research, Society and Development, 2021)
This article aims to affirm the role of the university in modern and contemporary social contexts. Methodologically, the article articulates insights from life experiences in university teaching, with a theoretical background capable of indicating the relevance of associating teaching, research and extension as a practical issue, in which epistemic, ethical-political and pedagogical dimensions are involved. As a result of its reflexive process, the challenge to preserve the best of universalism and sensitivity to the real arises, not succumbing to the simplistic vision of education, which is reduced to the specialization and technification demanded by the market. It points to the risk of succumbing to the pauperization of thought and to the erasure of critical capacity due to our inability to understand the world in which we live. It concludes that the procedural character of all knowledge and the radical historicity of any solution to our problems does not allow us to reach definitive solutions, but that we can understand ourselves, even partially, about what is the best solution, given the legal frameworks, the context and the subjects involved. The social legitimacy of university work depends on this ability.